THE SPECIFIC FEATURES OF THE PHASE I OF CLINICAL INVESTIGATIONS OF DRUGS - A. Y. Savchenko; G. V. Ramenskaya; V. G. Kukes (Сеченовский вестник, 2012)
This article discusses the possibility of clinical research of drugs, identifies the specific features of the phase I of clinical investigations.